Nutrition and Epigenetic Change in Insects: Evidence and Implications - Cridge, A.; Harrop, T.; Lovegrove, M.; Remnant, E.; Dearden, P.
Insects provide valuable model systems to help us understand the effects of nutrition on body form and life history traits. Insects often show very pronounced, extreme differences in phenotype in response to nutritional cues, and in recent years epigenetic mechanisms have been proposed as key to these responses. Here we review the links between nutrition, epigenetic change, and phenotype in a range of insects, focusing on evidence for epigenetic change linking nutrition and phenotype. While evidence exists that epigenetics plays a key role in responding to nutrition, we suggest that investigating the chain of causality from nutritional change to epigenetic change to phenotype is required before we can understand the role of epigenetics in insect nutrition.
Keywords: DNA METHYLATION; EPIGENETICS; HISTONE MODIFICATION; NUTRITION; PLASTICITY; POLYPHENISMS